Prospects for Receiving Paper from Agricultural Waste and Non-Wooden Alternative Materials - Alimova D. A.; Nabiyeva I. A. (International Journal on Integrated Education, 2022)
In this analytical article, the possibilities of using agricultural waste, non-wood and annual plants as a fibrous semi-finished product in the pulp and paper industry based on an analysis of the literature are examined. Scientific research conducted by scientists from around the world has been reviewed. The possibility of using alternative materials as raw materials in the paper industry was analyzed.